BRAYO CRISPY CHIPS INNOVATIVE PRODUCT BASED ON LOCAL WISDOM IN SAYUNG TO SUPPORT LEARNING OF SOCIAL SCIENCE “THE USAGE OF NATURAL RESOURCES” FOR GRADE V - Sulianto, Joko; Anggun Setiawan; Suci Rahayu (Schola, 2024)
Education is a crucial matter in shaping a nation’s future by fostering professional human resources equipped with knowledge and technology. This research explores the contributions of edupreneurship activities to children's development, focusing on fine motor skills, understanding basic economic concepts, and enhancing cognitive and social skills. Using a qualitative and participatory approach, this study involved 15 children at SD Negeri Purwosari 1 in hands-on activities related to the production of "BRAYO CRISPY CHIPS". The findings demonstrate significant improvements in fine motor coordination, as children engaged in tasks like measuring, pouring, and packaging, promoting essential motor skills. Additionally, the initiative fostered an understanding of fundamental economic principles through simulated financial transactions, cultivating economic literacy. Socially, the collaborative nature of the project enhanced teamwork, problem-solving abilities, and confidence among participants. This edupreneurship model not only supports the development of entrepreneurial attitudes in early childhood but also promotes holistic growth across cognitive, social, and physical domains. The study recommends integrating similar edupreneurship activities into early childhood curricula to further enhance independence, creativity, and problem-solving skills, while also suggesting avenues for future research to assess the long-term impacts of such educational interventions.